KONTRIBUSI PEMANFAATAN PERPUSTAKAAN DIGITAL DAN MINAT BACA TERHADAP INDEKS PRESTASI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK INFORMATIKA TAHUN MASUK 2012 JURUSAN ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Mutia Ahsanul Husna; Nelda Azhar; Titi Sriwahyuni (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This study aims to determine the contribution of the utilization of digital libraries and reading interests of students in the Faculty of Informatics Engineering at the State University of Padang to see the results of the achievement index of each student . This study is a correlational. Selection’s techniques of the informants in this study are using proportional random sampling , 54 respondents Department of Electronics Information Engineering Study Program . The technique of collecting data is using questionnaires and documentation class . Data were analyzed by used the statistical methods of correlation and regression . The results of data analysis showed : 1 ) The utilization of digital libraries contributed 18.5 % , for the results of achievement index , 2 ) for Reading students contributed 18.1 % , for the results of achievement index , 3 ) utilization of digital libraries and reading interests of students together contributed 24.9 % of the index results in the achievement of students majoring in informatics engineering education courses in the faculty of engineering , State University of Padang..